IFCEE 2021 Earth Retention, Ground Improvement, and Seepage Control - El Mohtar, Chadi; Kulesza, Stacey; Baser, Tugce; Venezia, Michael D. (American Society of Civil Engineers, 2021)
Selected papers from the International Foundations Congress and Equipment Expo 2021, held in Dallas, Texas, May 10-14, 2021. Sponsored by the International Association of Foundation Drilling (ADSC), the Deep Foundations Institute (DFI), the Pile Driving Contractors Association (PDCA), and the Geo-Institute of ASCE.This Geotechnical Special Publication contains 53 peer-reviewed papers on seepage control, ground improvement, and earth retention.Topics include: deflections in earth retention structures; mechanically stabilized earth; tall walls; Texas and soft soils; advances in ground improvement materials; ground compaction; bio and bioinspired ground improvement; slurry walls; ground densification; and ground improvement for seismic and static reinforcement.GSP 324 will be of interest to engineering practitioners, researchers, geotechnologists, contractors, and equipment manufacturers and suppliers in the deep foundation industry.
Keywords: Retaining walls -- Congresses.; Soil stabilization -- Congresses.; Seepage -- Congresses.; elektronické knihy; electronic books